Unions' Bargaining Coordination in Multinational Enterprises - Domenico Buccella (FIW - Research Centre International Economics, 2011)
This paper investigates the coordination of bargaining activities among labor unions in a Multinational Enterprise (MNE) with plants in different countries. Making use of a threestage game where the parties sequentially decide whether o coordinate negotiations, it derives the bargaining regimes arising as sub-game perfect equilibria. In presence of workers perfect substitutes in production and symmetry in the plants' efficiency, it is shown that unions' transaction costs may attenuate the conflict of interests among the parties as regards the level of coordination at which negotiations should take place.
Keywords: C78; F23; J51; D60; 330; bargaining; Multinational Enterprises; labor unions